Controlling the organization of phosphonium cations relative to p-sulfonatocalix[4]arene anions1. Issue 7 (21st February 2015) - Ling, Irene; Sobolev, Alexandre N.; Raston, Colin L.
<x xml:space="preserve">Abstract</x> A composite material containing supermolecules of 1, 4-bis(triethylammoniomethyl)benzene and p-sulfonated calix[4]arene involves preferential binding of the ammonium moieties in the cavities of two geometrically opposed calixarenes with mono-phosphonium cations arranged in the endo-orientation with respect to the calixarene bilayers, as a multi-layered structure.